Preoperative Sublingual Misoprostol in Reducing Intraoperative Blood Loss During Abdominal Hysterectomy - Atchara Panichpongpan; Chonthicha Satirapod; Puchong Likittanasombat; Nathpong Israngura Na Ayuttaya (The Royal Thai College of Obstetricians and Gynaecologists, 2014)
Objective:To study the effectiveness of a pre-operative single dose sublingual misoprostol for reducing blood loss of abdominal hysterectomy with/without salpingo-oophorectomy performed for symptomatic uterine leiomyomas.Materials and methods: A total of 70 women undergone total abdominal hysterectomy with/without salpingo-oophorectomy for symptomatic uterine leiomyoma between June 2012 to January 2013 was double-blindly randomized into two groups to receive two tablets of misoprostol (200 microgram each) sublingual (n= 35) or two placebo tablets vitamin B6 (100 milligram each) sublingual (n=35) at 30-60 minutes before the operation. The amount of intra-operative blood loss, the change in haemoglobin level after the operation, the requirement for blood transfusion and the incidence of side effects were recorded.Result:Our data showed no significant difference between two groups in term of intraoperative blood loss. (misoprostol, mean 549.6 ± 391.9 ml versus placebo, mean 445.0 ± 270.6 ml, p=0.20) Moreover there were no observed differences in the need for postoperative blood transfusion, the change in hemoglobin level after the operation and side effects profiles between the two groups.Conclusion: We concluded that a single preoperative dose of sublingual misoprostol is not effective in reducing intraoperative blood loss and need for post-operative blood transfusion after total abdominal hysterectomy with/without salpingo-oophorectomy for symptomatic uterine leiomyomas.